Co‐ordinating Co‐ordination: The European Commission and the Culture Open Method of Co‐ordination*. (9th July 2017) - Mattocks, Kate
Abstract: This article examines the role of the European Commission in non‐legislative policy co‐ordination in the European Union. Using the Open Method of Co‐ordination (OMC) in the oft‐neglected sector of cultural policy as a case study, it argues that rather than a neutral facilitator as it appears on paper, the Commission occupies both a political and administrative leadership role in the operation of the culture OMC. Through analysis of policy documentation, interviews and non‐participant observation material, the article demonstrates how the Commission has operated as a key driver and agenda‐setter in the field, exposing the inter‐institutional dynamics in a competence in which the EU has a supporting role. The findings thus have broader implications for the study of agenda‐setting and European integration in policy sectors where the EU holds a supporting competence.